The impact of physical activity on the quality of life of a sample of Italian people with physical disability - Biagini, Alessia; Bastiani, Luca; Sebastiani, Laura (Frontiers in Sports and Active Living, 2022)
Physical activity promotes psychophysical health, however, to date, only few studies have investigated the association between regular physical activity and the quality of life perception and satisfaction in disabled persons. Our aim was to compare the quality and satisfaction for life, self-efficacy and personal wellbeing of two samples of Italian people with physical disability (amputation, spinal cord dysfunction, neurological disability), one who practiced regular physical activity (Active group, n=33), the other consisting of sedentary individuals (Inactive group, n=26). We compared the groups’ mean scores in the WORLD HEALTH ORGANIZATION Quality of Life questionnaire (WHOQOL-BRIEF), the Personal Wellbeing Index, and the Satisfaction With Life and General Self-Efficacy Scales. We also compared the impact of rehabilitation, sport, family support, income, job/school and raising a family on social life and life quality by means of separate MANOVAs. Results of the WHOQOL showed better quality of life in the Active than the Inactive group (overall QOL, 4.09±0.7 vs 3.50±0.9; Psychological domain, 72.09± 12.7 vs 62± 21.6; Social Relationships domain, 76.54± 16.4 vs 59.52±24.2). No difference was found for satisfaction with health and life, personal wellbeing and self-efficacy. The impact of sport on social life and quality of life was greater in Active than in Inactive individuals. Findings suggest positive effects of physical activity on the perception of quality of life in disabled people. However, they do not allow to disentangle whether physical activity is practiced by patients with good quality of life or whether physical activity is responsible for better quality of life.